Ritual Nyadhar, Ecology and Gender - Khomsiyatul Mukarromah (MUHARRIK: Jurnal Dakwah dan Sosial, 2022)
Nyadhar is a ritual to build togetherness to show gratitude for the gift of salt as a source of livelihood, hope, prayer for salvation, and blessings of Life in the future. Nyadhar is an ecologically oriented ritual only held in the salt pond area, it’s done by the local community, and surrounding areas. Not only the ecological perspective but the gender perspective is also shown in the rituals. This study aims to explain ecology and the role of Madurese women in nyadhar rituals, especially in salt ponds in Pinggir Papas village, in Sumenep Regency. This research was conducted with an ethnographic approach with data collection techniques from several sources, including literature study, participatory observation, and interviews. This ritual shows the perfect relationship between God, nature, and humans. The nyadhar ritual shows the peculiarities of ritual in the salt pond ecology, firstly, the relationship of actor networks between men and women in various circles. Second, special equipments in rituals. Every man and woman has a steady, permanent role that cannot be fought for. The role is not seen as competition but as order and conformity.